2021
DOI: 10.1159/000514381
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Children, Adolescents, and Young Adult Cancer Survivors

Abstract: <b><i>Background and Summary:</i></b> Thanks to increasing cure rates to currently &#x3e;80%, children, adolescents, and young adults (CAYA) survive their cancer much more frequently today than decades ago. Due to their long life expectancy, CAYA cancer survivors are at a particular risk of long-term sequelae from the cancer itself or the therapy applied; this requires specific follow-up, and preventative or even therapeutic interventions. Thus, compared to the normal population, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
0
19
0
2
Order By: Relevance
“…Notably, radiation treatment of childhood cancer appears to be associated with significant increases in breast cancer risk, comparable to those reported in females with a BRCA gene mutation [ 39 , 40 ]: both BRCA and certain radiation treatments carry similarly high risks compared to the cumulative population incidence of breast cancers diagnosed before age 45, namely 12–16% in patients treated with radiation as children, 13–20% in women with a BRCA mutation, and 1% in the general population [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The large size of the increased risk of breast cancer in females exposed to radiation in childhood led to the development of specific recommendations for breast cancer surveillance for female survivors of childhood, adolescent, and young adult cancer given chest radiation [ 41 ], as recommended for women harboring harmful BRCA mutations [ 42 ].…”
Section: Sex and Age Modulate Secondary Cancers Attributable To Exter...mentioning
confidence: 93%
See 1 more Smart Citation
“…Notably, radiation treatment of childhood cancer appears to be associated with significant increases in breast cancer risk, comparable to those reported in females with a BRCA gene mutation [ 39 , 40 ]: both BRCA and certain radiation treatments carry similarly high risks compared to the cumulative population incidence of breast cancers diagnosed before age 45, namely 12–16% in patients treated with radiation as children, 13–20% in women with a BRCA mutation, and 1% in the general population [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The large size of the increased risk of breast cancer in females exposed to radiation in childhood led to the development of specific recommendations for breast cancer surveillance for female survivors of childhood, adolescent, and young adult cancer given chest radiation [ 41 ], as recommended for women harboring harmful BRCA mutations [ 42 ].…”
Section: Sex and Age Modulate Secondary Cancers Attributable To Exter...mentioning
confidence: 93%
“…The best source of information on the effects of therapeutic radiation on secondary cancer risk derive from survivors of Hodgkin’s Lymphoma (HL) treated with radiation, who have been observed in a number of studies designed to monitor the rate of secondary cancers in this population over an extended time period [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. While much smaller in scope than the atomic bomb survivor studies, these studies consistently found an increased rate of solid tumors in HL patients treated with external radiation [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], although, like in atomic bomb survivors (above), the risks were modulated by age at exposure, sex and site of cancer. Thus, HL patients treated with external radiation have a higher incidence of all solid cancers except for prostate [ 28 ], and the largest increase was in (female) breast cancer.…”
Section: Sex and Age Modulate Secondary Cancers Attributable To Exter...mentioning
confidence: 99%
“…Among approximately 50-70% of adult and 20-50% of pediatric survivors of HSCT, cGvHD is observed ( 82 84 ). cGvHD symptoms and treatment are often associated with significant morbidity and decreased functional status and quality of life ( 11 , 85 , 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach is highlighted in several studies in adults [28][29][30][31][32]. In the paediatric group, these data are still presented only sparsely [33,34].…”
Section: Discussionmentioning
confidence: 75%